Gray's anatomy for students - Drake, Richard L. (Richard Lee) 1950-; Vogl, Wayne; Mitchell, Adam W. M. (Churchill Livingstone/Elsevier, 2015)
Anatomy texts just don't get any better than Gray's Anatomy for Students! Now in its 3rd edition, this completely revised medical textbook continues its focus on just the core information you need for your anatomy courses, presenting everything in an easy-to-read, visually appealing format that facilitates study.